PELAKSANAAN PERLINDUNGAN HAK TERSANGKA DALAM MEMBERIKAN KETERANGAN SECARA BEBAS PADA TINGKAT PENYIDIKAN DI KEPOLISIAN SEKTOR LIMAPULUH KOTA PEKANBARU - Firman Saputra. A; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
In each stage of the examination, especially in the examination at the stage of investigation, the right to give particulars had to be given to the suspect. As set out in Article 52 of Law No. 8 of 1981 on Criminal Procedure, there is said that: In the inspection process at the level of investigation and trial, the suspect or defendant is entitled to give information freely to the investigator or a judge. It is clear that the suspect or defendant since under examination at the level of investigation has been allowed to enjoy or acquire rights, one of which is the right to testify freely. Where the rights of the accused constitute a guarantee of human rights.This type of research is classified as socio-juridical research, because this research author directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined. This research was conducted in the Police Sector Fifty cities Pekanbaru, while the sample population is a whole party with regard to the issues examined in this study, the data source used, primary data, secondary data, and the data tertiary, data collection techniques in this research with interviews, questionnaires, and literature study.The research problems are, among others: first, How the implementation of the protection of the rights of suspects in providing information freely on the level of investigation in the Police Sector Fifty cities Pekanbaru, second, whether the obstacles in the implementation of the protection of the rights of suspects in providing information freely on the level of investigation in the Police Sector Fifty cities Pekanbaru, third, how to overcome obstacles in the implementation of the protection of rights of the accused freely testified at the level of investigation in the Police Sector Fifty cities Pekanbaru. Results of the study are: first, Implementation protection of the rights of suspects in providing information freely to the process of checking the level of investigation in police Fifty cities Pekanbaru is still not running well, because in practice is still a suspect who feels that he does not get this right, second, Areas of law enforcement officers, community factors, factors issues infrastructure is not maximized, third, police were professional and high integrity, existence of facilities and pre adequate facilities, implement and uphold human rights, community participation and outreach to the community so that people know rights and obligations.Keywords: Rights of Suspects - Description Freely - Investigation